EVALUATION OF IMPLEMENTATION OF LOCAL GOVERNMENT INFORMATION SYSTEM (SIPD) : Case Study on Secretariat Office of The Council of Representatives Serang City - Angga Nugraha (Review of Accounting and Taxation, 2022)
Purpose - The purpose of this paper was to find out how the impact of the implementation of SIPD and to find out how the efforts of the Serang City DPRD Secretariat to continue to implement SIPD Design/methodology/approach - The method used in this research is descriptive qualitative research methods. The technique used in data collection where the source of the data obtained is primary and secondary data Finding - Secretariat DPRD Serang City has used SIPD in its fiscal management, starting from the planning process to administration. However, several obstacles occur because the system is note-perfect or there are still many disadvantages that it has an impact on several things including employees having to adapt to tea new systems, changes in payment methods, lack of time efficiency, difficulty in disbursing funds, and having to do two collections. The Secretariat of tea DPRD of serang City made efforts to observe the obstacles that occurred, namely by using a package system, so that financial governance continued to run according to established policies. Originality - This is your opportunity to provide readers with an analysis of the value of your results. It is a clever idea to ask colleagues whether your analysis is balanced and fair and again, it is important not to exaggerate. You can also conjecture what future research steps could be.